Individualized Endoscopic Surveillance for Metachronous Gastric Cancer After Endoscopic Submucosal Dissection: A Retrospective Observational Study - Huang, Keting; Jin, Duochen; Zhang, Guoxin (Turkish Journal of Gastroenterology, 2023)
Background: Endoscopic submucosal dissection has been widely applied for curative resection of early gastric cancer or high-grade dysplasia, and metachronous gastric cancer is a major issue after endoscopic therapy. Here, we studied the recurrence patterns of metachronous gastric cancer and its correlation with the primary lesions. Methods: A total of 286 consecutive patients undergoing endoscopic submucosal dissection for early gastric cancer or high-grade dysplasia between March 2011 and March 2018 were retrospectively reviewed. Metachronous gastric cancer was defined as a new gastric cancer detected more than 1 year after endoscopic submucosal dissection. Results: During a median follow-up of 36 months, 24 patients developed metachronous gastric cancer. The 5-year cumulative incidence was 13.4% and the annual incidence was 24.3 cases per 1000 person-years. Subgroup analysis revealed that the third year after early gastric cancer resection and the fifth year after high-grade dysplasia resection were the predilection periods of metachronous gastric cancer. Correlation analysis suggested that the metachronous and primary lesions showed a significant correlation in cross-sectional position (C = 0.627, P = .027) but not in pathological characteristics (P > .05). When the primary lesions were located in the posterior walls, the metachronous lesions were prone to occur in the lesser curvatures (C = 0.494, P = .008) and the reverse was also true (C = 0.422, P = .029). Conclusions: The predilection periods and common sites of metachronous gastric cancer are associated with the primary lesions. Meticulous individualized endoscopic surveillance after endoscopic submucosal dissection requires to be conducted, taking into account the characteristics of primary lesions.